2007
DOI: 10.1105/tpc.107.050153
|View full text |Cite
|
Sign up to set email alerts
|

PIL5, a Phytochrome-Interacting bHLH Protein, Regulates Gibberellin Responsiveness by Binding Directly to theGAIandRGAPromoters inArabidopsisSeeds

Abstract: Previous work showed that PHYTOCHROME-INTERACTING FACTOR3-LIKE5 (PIL5), a light-labile basic helix-loop-helix protein, inhibits seed germination by repressing GIBBERELLIN 3beta-HYDROXYLASE1 (GA3ox1) and GA3ox2 and activating a gibberellic acid (GA) catabolic gene (GA2ox2). However, we show persistent light-dependent and PIL5-inhibited germination behavior in the absence of both de novo GA biosynthesis and deactivation by GA2ox2, suggesting that PIL5 regulates not only GA metabolism but also GA responsiveness. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
508
3
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 421 publications
(550 citation statements)
references
References 67 publications
31
508
3
4
Order By: Relevance
“…Linearised plasmids encoding BRM, BRM , ATSWI3C and a PP2A PCR product were used to generate standard curves. The gene-speciWc primers used for BRM splice variant proWling and measurements of BRM and ATSWI3C expression levels, as well as for PP2A (as described previously by Oh et al 2007) are listed in Table S1. Final concentrations of qRT-PCR primers were 0.5 M and the annealing temperature was set at 60°C in all assays.…”
Section: Brm Antibody and Western Blottingmentioning
confidence: 99%
“…Linearised plasmids encoding BRM, BRM , ATSWI3C and a PP2A PCR product were used to generate standard curves. The gene-speciWc primers used for BRM splice variant proWling and measurements of BRM and ATSWI3C expression levels, as well as for PP2A (as described previously by Oh et al 2007) are listed in Table S1. Final concentrations of qRT-PCR primers were 0.5 M and the annealing temperature was set at 60°C in all assays.…”
Section: Brm Antibody and Western Blottingmentioning
confidence: 99%
“…A germination study of multiple DELLA protein mutants suggested that RGL2 is the predominant repressor of Arabidopsis seed germination in the light and GAI, RGA, and RGL1 enhance the function of RGL2 (Cao et al, 2005). Recently, RGA and GAI have been shown to play a role in inhibiting germination of dark-imbibed seeds in the absence of active phytochromes (Oh et al, 2007). DELLA proteins other than RGL2 may enhance RGL2 function also in supraoptimal temperature conditions.…”
Section: Function Of Ga Negative Regulators On Thermoinhibitionmentioning
confidence: 99%
“…reported to control other light-regulated responses such as chlorophyll biosynthesis 27 or seed germination 28 -processes that are also known to be modulated by DELLAs. Hence, competitive interaction with members of the PIF family of transcription factors might be a prevailing mechanism for DELLA function, serving to explain the great diversity of responses controlled by these repressors.…”
Section: S-pif4mentioning
confidence: 99%